Writing differently by experiencing ‘aesthetic episodes’ as a researcher ‒ vulnerable insights from the field - Suvi Satama (My University, 2022)
This paper aims at reflecting upon the value of aesthetic experiences of the researcher in academic writing. More specifically, this paper explores the ways we can write differently about organizational phenomena by experiencing ‘aesthetic episodes’ in the field. In this paper, I share examples of the ‘aesthetic episodes’ that I as a researcher have experienced during three different research projects. I find these examples as a way to elaborate on ethical and more sensory appreciative approaches to writing, as well as develop questions around voicing marginal research areas in organization studies. The paper identifies three aspects: appreciating ‘sensory cues’, writing ‘in and from the flesh’, and allowing vulnerability to flourish, which allow the researcher to experience ‘aesthetic episodes’ in the field. This paper argues that by experiencing ‘aesthetic episodes’ as researchers we can challenge the hegemonic and masculine traditions of academic writing, and develop the ways we write in academia into a more delicate and vulnerable directions.
Proceedings of EURAM18 European Academy of Management conference 2018